2020
DOI: 10.24820/ark.5550190.p011.308
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of thiadiazoles, oxadiazoles, triazoles and thiazoles

Abstract: Drugs containing the heterocyclic five-membered thiadiazoles and isosteres possess a wide range of biological activities, including but not limited to, antiviral, antifungal, antihistamine, anticancer. In this study, we list the agents containing thiadiazoles and isosteres which are reported to have antiviral activity. We believe that this compilation will be a useful resource for researchers working in the field of antiviral agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…The electrophilic addition of halogens to cyclic enol ethers has been investigated earlier by Lemieux and Fraser-Reid [ 39 ], who proposed a general mechanism involving the initial formation of carbenium ions which, upon nucleophilic attack by halide ion, give mainly the products of thermodynamic control. Later on, it has been shown that the product formation is under kinetic control and that the stereoselectivity depends on the solvent polarity [ 7 , 9 , 10 ], the structure of the enol ether, and the nature of the halogen [ 16 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophilic addition of halogens to cyclic enol ethers has been investigated earlier by Lemieux and Fraser-Reid [ 39 ], who proposed a general mechanism involving the initial formation of carbenium ions which, upon nucleophilic attack by halide ion, give mainly the products of thermodynamic control. Later on, it has been shown that the product formation is under kinetic control and that the stereoselectivity depends on the solvent polarity [ 7 , 9 , 10 ], the structure of the enol ether, and the nature of the halogen [ 16 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…1,3,4-Thiadiazole represents an important heterocyclic scaffold due to its pharmacological activity. Their derivatives exhibit various and significant activities such as antibacterial [ 1 ], antifungal, anti-inflammatory [ 2 ], anti-tuberculosis [ 3 ], antidepressant [ 4 ], and anticancer [ 5 , 6 , 7 ] activities, etc. The 1,3,4-Thiadiazole ring influences cancer cell lines mainly due to ability of nitrogen atoms to donate electrons and form hydrogen bonds or chelate certain metal ions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By applying microwave technology, different oxadiazole derivatives can be synthesized and also screened to find out new therapeutic molecules with diverse biological activities such as antibacterial, antifungal, antidepressant, antitubercular and antiinflammatory, etc. [ 71 , 72 , 73 , 74 ]. Hence, oxadiazole is considered a significant heterocyclic core and becomes a major scaffold for the development of new drug candidates because of its potential to be involved in the binding interactions with different targets or receptors with suitable metabolic profile [ 75 , 76 , 77 , 78 ].…”
Section: Future Developmentmentioning
confidence: 99%
“…Heterocyclic compounds specially the five membered (thiazoles, thiadiazoles, triazoles, 1,3,4-oxadiazoles and benzimidazole ring) have shown a very interesting biological activity [ 8 ]. These compounds also showed very promising antiviral activity against different viruses [ 9 ]. Triazole based derivatives has been attracting the researcher's attention due to its effectiveness as therapeutic drugs in the field of antibacterial, antiviral, antifungal, antitumor and antihypertensive agents.…”
Section: Introductionmentioning
confidence: 99%